Architecture of transpressional thrust faulting in the San Bernardino Mountains, southern California, from deformation of a deeply weathered surface - Sieh, Kerry (2012)
To investigate the architecture of transpressional deformation and its long-term relationship to plate motion in southern California, we have studied the deformation pattern and structural geometry of orogeny within the San Andreas fault system. The San Bernardino Mountains have formed recently at the hub of several active structures that intersect the San Andreas fault east of Los Angeles. This mountain range consists of a group of crystalline blocks that have risen in association with transpressive plate motion along both high- and low-angle faults of a complex structural array. We have used a deeply weathered erosion surface as a structural datum to constrain the pattern of vertical deformation across fault blocks in and adjacent to this mountain range. By subtracting the hanging wall and footwall positions of this preuplift horizon we have determined vertical displacement along two major thrust faults. We conclude that one fault, the North Frontal thrust, has played a more significant role in raising the large fault blocks and can explain the uplift of all but a few crustal slivers. On the basis of the pattern of displacement associated with this thrust fault we have also inferred fault zone geometry beneath the range. Rather than simply steepening into a high-angle fault zone or flattening into a decollement, the thrust fault may have a complex, curviplanar geometry. The pattern of rock uplift also enables us to calculate the total motion accommodated by this orogeny. We estimate that >6 km of convergence (5% of the total plate motion in the last 2 Myr) has occurred. This horizontal shortening is associated spatially with the 15-km-wide restraining bend in the San Andreas fault zone near San Gorgonio Pass. The entire range may thus have risen because of a small geometric complexity in the San Andreas fault rather than the obliquity of far-field plate motion.